PENERAPAN MODEL GAME-BASED LEARNING UNTUK MENINGKATKAN PARTISIPASI SISWA DALAM PEMBELAJARAN FIQIH PADA KELAS IV MADRASAH IBTIDAIYAH AL-ISLAMIYAH TUNGGULPAYUNG - Nikmah, Nadiyatun (Study Program of Madrasah Ibtidaiyah Teacher Education at Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
This research evaluates the application of the Game-Based Learning model in increasing student participation in Fiqh learning at Madrasah Ibtidaiyah Al-Islamiyah, Indramayu. Using the Classroom Action Research (PTK) method with two cycles, this research involves planning, implementation, observation and reflection. Data was collected through participation tests, class observations, and questionnaires. The results show that Game-Based Learning significantly increases students' participation, understanding and motivation in learning Fiqh. This model also creates an interactive and fun classroom atmosphere. In conclusion, Game-Based Learning is an effective strategy in increasing student involvement and understanding and can be a reference for developing innovative learning methods.